Reusable Polybenzimidazole Nanofiber Membrane Filter for Highly Breathable PM 2.5 Dust Proof Mask - Lee, Sol; Cho, A Ra; Park, Daehoon; Kim, Jae Kyeom; Han, Kyung Seok; Yoon, Ick-Jae; Lee, Min Hyung; Nah, Junghyo (ACS applied materials & interfaces, 2019)
Ultrafine particulate matters (PMs) are an imminent threat to the human respiratory system, as their sizes are comparable to and even smaller than human tissues. To cope with this situation, researchers have developed and commercialized various personal dust proof masks. However, because of the relatively thick filter membrane to guarantee filtering efficiency, a huge pressure drop across the active filter layer is inevitable and breathing through it becomes uncomfortable. In this work, we investigated the performance of electrospun polybenzimidazole (PBI) nanofiber membrane filters that can potentially be used for dust proof masks or other high-performance filters. Thanks to its high dipole moment (6.12) as confirmed by density functional theory (DFT) calculation, the surface potential of the PBI nanofiber air filter, measured by KPFM, was higher than that of other commercially available mask filters. The filter developed in this work provides high PM filtering efficiency of ∼98.5% at much reduced pressure drop (130 Pa) in comparison to those used in commercially available masks (386 Pa) with similar filtering efficiencies. Consequently, an approximately 3-fold higher quality factor (∼0.032), evaluated for PM , in comparison to that of commercial ones (∼0.011) was achieved by using PBI nanofiber. Furthermore, we developed a cleaning method effective for the filter contaminated by both inorganic and organic PMs. Even after several cycles of cleaning, the PBI filter membrane demonstrated negligible damage and retained its original performance because of its mechanical, thermal, and chemical durability.